Pengaruh Pemeriksaan Pajak dan Penagihan Pajak Terhadap Penerimaan Pajak Penghasilan 25/29 Badan (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Majalaya) - Octavia, Jayanthi; Wulandari, Yuanita Retno (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2022)
This study is based on the phenomenon that occurs in the tax examination was still high namely the Letter of Tax Underpayment was caused by low awareness of taxpayers in paying tax so that in tax revenue there was still acceptance doesn't reach the target and that occured in the tax collection was letter issue contained warning caused by the low compliance of taxpayers so that in tax revenue there is still acceptance that does not reach the target.The purpose of this study was to determine the influence of tax audit and tax collection on the corporate income tax revenue 25/29. In this study used descriptive and verification method with quantitive approach. Data was analyzed statistically by using multiple linear regression analysis,correlation analysis, determinant coefficient analysis and hypotesis test(t test).The result of this study indicated a strong influence of tax audit on corporate income tax revenues 25/29 and tax collection on corporate income tax revenue 25/29.